2020
DOI: 10.1021/acs.jpcb.9b11345
|View full text |Cite
|
Sign up to set email alerts
|

Space Size-Dependent Transformation of Tetraphenylethylene Carboxylate Aggregates by Ice Confinement

Abstract: Tetraphenylethylene carboxylate (TPEC) aggregates are transformed by ice confinement, which is controlled by the initial concentration of sucrose employed as a cryoprotectant and temperature. The freezing of aqueous sucrose leads to the formation of micro- or nanoliquid phase confined in ice. Aggregation-induced emission (AIE) of tetraphenylethylene carboxylate (TPEC) in the ice-confined space is explored using fluorescence spectroscopy and lifetime measurements. The characteristics of AIE in the ice-confined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…However, α-CD and β-CD had no significant effect on the absorption of TPE-SGA (Figure b). It is known that the self-assembly of TPE derivative tends to afford fluorescent J-aggregates concomitant with a bathochromic shift. In contrast, the disassembly of J-aggregates would lead to a hypsochromic shift of absorption. Therefore, the hypsochromic effect induced by the addition of γ-CD indicates the deaggregation of TPE-SGA.…”
Section: Resultsmentioning
confidence: 99%
“…However, α-CD and β-CD had no significant effect on the absorption of TPE-SGA (Figure b). It is known that the self-assembly of TPE derivative tends to afford fluorescent J-aggregates concomitant with a bathochromic shift. In contrast, the disassembly of J-aggregates would lead to a hypsochromic shift of absorption. Therefore, the hypsochromic effect induced by the addition of γ-CD indicates the deaggregation of TPE-SGA.…”
Section: Resultsmentioning
confidence: 99%
“…(4) In FCSs, some unusual chemical phenomena including the acceleration of chemical reactions under subzero conditions and dissolution of chemical species insoluble in water have been reported. (5)(6)(7)(8)(9)(10)(11)(12) These effects are attributed to the unique physicochemical properties of FCSs, induced by the microscale phase transitions at ice/solution interfaces. (13)(14)(15) The reductive reactions of metal oxides and their dissolution have also been reported to be accelerated in FCSs.…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena could not be interpreted solely by freeze concentration. We have suggested that the interface between ice and a solution phase (freeze concentrated solution, FCS) should play an essential role because most of the freeze-specific phenomena become more marked as the interface/volume ratio increases. In the present work, we studied the redox behaviors of iron oxides using cyclic voltammetry (CV) in frozen solutions and found some interesting freeze-specific phenomena; hereinafter, we call this method “freeze CV” to distinguish it from usual CV in solutions. , Freeze CV allows us to study phenomena that occur at the electrode interface with the FCS. A use of an electrode, in which iron oxides are incorporated, is expected to provide information on the redox processes of the iron oxides at the FCS interface and to allow us to discuss the freeze effects on their behaviors.…”
mentioning
confidence: 96%
“…We have reported some interesting freeze-specific phenomena, including enhanced dissolution of organic compounds, enhanced complexation of crown ethers, acceleration of pseudo-first-order reaction, and so forth. These phenomena could not be interpreted solely by freeze concentration.…”
mentioning
confidence: 99%